Correction: Polyhydroxyalkanoates as biomaterials. Issue 4 (5th April 2019) - Thorat Gadgil, Bhagyashri S.; Killi, Naresh; Rathna, Gundloori V. N.
Abstract : Correction for 'Polyhydroxyalkanoates as biomaterials' by Bhagyashri S. Thorat Gadgil et al., Med. Chem. Commun., 2017, 8, 1774–1787.